Comparative study of abdominal ultrasonography in South American small feline in captivity - Grandez R., Ricardo (2021)
The topography, morphology, ecotexture, echogenicity and architecture of the abdominal organs of four species of wild feline native to Peru were described through ultrasonography to generate ultrasound parameters in the smaller felines and obtain comparative measurements between these species. The felines were in a zoo in Lima, Peru: two ocelots (Leopardus pardalis), two oncillas (L. tigrinus), three margay (L. wiedii) and four Pampas cats (L. colocolo). An Esaote ultrasound equipment, model MyLab One Vet with convex transducer SC3123 was used. The characteristics of the abdominal organs of the studied species were similar in location, shape, echogenicity and ecotexture to those previously described in margay and domestic cats. The dimensions of the organs presented a variation according to the size of each species; being largest in the ocelot, followed by the margay, the Pampas cat, and finally the oncilla.